ANALYZING THE POTENTIAL OF ESPORTS AS A MAINSTREAM ENTERTAINMENT MEDIA: A STUDY - Lintang Rumi Sutrisno, Ahmad
This research is conducted to find and determine the perks the public can get by engaging in Esports, the negative effects that can affect Esports and making suggestions on how to improve the Esports scene. Relevant literatures and articles are used to gather primary data required for the research. This study will be based on interaction in Esports, viewership in Esports, toxicity and aggressive behavior in Esports, as well as in-game purchases in Esports. Esports can be defined as a nontraditional sport that uses technology to make participants exempt from direct physical activities. It is discovered that three primary attributes – competition, challenge and escapism can be associated with Esports. To add, interactivity and competition are primary elements that usually motivates video gaming. Not only coming to live events, viewership in Esports also comes from broadcasting channels and online streaming platforms. Esports have a large following via online streaming platforms such as Twitch and Youtube. Despite its potential, gaming and Esports in common have a problem in the shape of toxicity and aggressive behavior. It is found in one of the literatures used that playing a violent video game for 15 minutes can produce elevated levels of aggressive behavior that lasts between 5 and 10 minutes. To add, Esports players tend to express their satisfaction, especially in the heat of the moment with expletives, hurling verbal abuse towards their opponents. To gain profit from video games, game developers usually provide in-game transaction systems in their games, commonly dubbed “microtransactions”. These microtransactions commonly are in-game items that can be bought for real money, giving the players some sort of gratification. Another notable transaction commonly happening in Esports are gambling in Esports matches. Massive interest in Esports that are followed by an equally massive audience has led to most major betting operators to include Esports matches in their daily gambling offer. It is important to note that these transactions can be considered as exploitative, if not predatory, especially since they are accessible to underage players.